2017
DOI: 10.1101/gr.226050.117
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of noncanonical translation initiation sites through mass spectrometric analysis of protein N termini

Abstract: Translation initiation generally occurs at AUG codons in eukaryotes, although it has been shown that non-AUG or noncanonical translation initiation can also occur. However, the evidence for noncanonical translation initiation sites (TISs) is largely indirect and based on ribosome profiling (Ribo-seq) studies. Here, using a strategy specifically designed to enrich N termini of proteins, we demonstrate that many human proteins are translated at noncanonical TISs. The large majority of TISs that mapped to 5' untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 31 publications
(57 reference statements)
9
84
0
Order By: Relevance
“…However, most studies focused their analysis on the transcripts' girst 100 nucleotides, and thus did not investigate the downstream truncations that were commonly disregarded as cryptic transcripts. A similar phenomenon has been described in human cells, where alternative N-terminal proteoforms can lead to different protein stability (Gawron et al 2016;Na et al 2018). Regardless of their origin, it is clear that truncated proteins can have signigicant phenotypical impacts such as changes in protein localization (Carlson et al 1983) or may even act as dominant-negative factors opposing the function of the full-length protein (Ungewitter and Scrable 2010).…”
Section: Discussionsupporting
confidence: 62%
“…However, most studies focused their analysis on the transcripts' girst 100 nucleotides, and thus did not investigate the downstream truncations that were commonly disregarded as cryptic transcripts. A similar phenomenon has been described in human cells, where alternative N-terminal proteoforms can lead to different protein stability (Gawron et al 2016;Na et al 2018). Regardless of their origin, it is clear that truncated proteins can have signigicant phenotypical impacts such as changes in protein localization (Carlson et al 1983) or may even act as dominant-negative factors opposing the function of the full-length protein (Ungewitter and Scrable 2010).…”
Section: Discussionsupporting
confidence: 62%
“…Recent research showed that there is more heterogeneity in gene models than previously anticipated, as a result of e. g. alternative translation initiation sites (aTIS) (Na et al 2018) and there is an on-going debate in the community whether or not long non-coding RNAs (lncRNAs) can be translated into proteins (Chen et al 2017). Ribosomal profiling showed that thousands of potential aTIS may exist and that ~40% of all lncRNAs can at least engage the ribosome (Kearse and Wilusz 2017).…”
Section: Proteogenomic Characterisation Of Human Tissuesmentioning
confidence: 99%
“…A straight forward approach would be to use mass spectrometry to detect uORF derived peptides; however this has previously been proven difficult, likely due to a range of complications from sample preparation, bias in annotation algorithms, as well as intrinsic factors that make these peptides difficult to detect (Bazzini, Johnstone et al 2014, Chugunova, Navalayeu et al 2018. Several methods have been developed to enhance the detection of small peptides, each with variable yields (Slavoff, Mitchell et al 2013, Bazzini, Johnstone et al 2014, Na, Barbhuiya et al 2018.…”
Section: Characterization and Experimental Validation Of Spectre-idenmentioning
confidence: 99%